Solving the Lane-Emden Equation within a Reproducing Kernel Method and Group Preserving Scheme - Hashemi, Mir Sajjad; Akgul, Ali; İnç, Mustafa; Mustafa, Idrees Sedeeq; Baleanu, Dumitru (Mdpi, 2017)
We apply the reproducing kernel method and group preserving scheme for investigating the Lane-Emden equation. The reproducing kernel method is implemented by the useful reproducing kernel functions and the numerical approximations are given. These approximations demonstrate the preciseness of the investigated techniques.
Keywords: Lane-Emden equation; group preserving scheme; reproducing kernel functions; approximate solutions